Evaluation of first metatarsal head declination through a modified distal osteotomy in hallux rigidus surgery. A cadaveric model. Issue 3 (September 2015) - Asunción, Jordi; Poggio, Daniel; Pellegrini, Manuel J.; Melo, Rodrigo; Ríos, José
Highlights Modified distal metatarsal osteotomy in hallux rigidus. Declination effect. Avoid metatarsal shortening and transfer metatarsalgia.